Entropy squeezing for qubit - field system under decoherence effect - Abdel-Khalek, Sayed; Berrada, Kamal; Obada, Abdel-Shafy Fahmy; Wahiddin, Mohamed Ridza (Kvantovaya Elektronika and Turpion Ltd, 2014)
We study in detail the dynamics of field entropy squeezing FES) for a qubit - field system whose dynamics is described by the phase-damped model. The results of calculations show that the initial state and decoherence play a crucial role in the evolution of FES. During the temporal evolution of the system under decoherence effect, an interesting monotonic relation between FES, Wehrl entropy (WE)and negativity is observed.